2021
DOI: 10.1016/j.bioactmat.2020.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Cyanine conjugates in cancer theranostics

Abstract: Cyanine is a meritorious fluorogenic core for the construction of fluorescent probes and its phototherapeutic potential has been enthusiastically explored as well. Alternatively, the covalent conjugation of cyanine with other potent therapeutic agents not only boosts its therapeutic efficacy but also broadens its therapeutic modality. Herein, we summarize miscellaneous cyanine–therapeutic agent conjugates in cancer theranostics from literature published between 2014 and 2020. The application scenarios of such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 96 publications
(112 reference statements)
0
40
0
Order By: Relevance
“…Cyanine core is among the most investigated fluorophores due to its favorable optical properties such as high molar absorptivity, narrow absorption/emission bands, reasonable fluorescence quantum yield, and most importantly, tunable fluorescence profile from the UV–vis to NIR range ( Delaey et al, 2000 ; Mishra et al, 2000 ; Kulbacka et al, 2011 ; Bhattarai and Dai, 2017 ; Li Y. et al, 2020 ; Li et al, 2021 ). Additionally, the excellent biocompatibility and low toxicity make them a great candidate for biological studies spanning from imaging to therapy.…”
Section: Cyanine Dyes In Phototherapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanine core is among the most investigated fluorophores due to its favorable optical properties such as high molar absorptivity, narrow absorption/emission bands, reasonable fluorescence quantum yield, and most importantly, tunable fluorescence profile from the UV–vis to NIR range ( Delaey et al, 2000 ; Mishra et al, 2000 ; Kulbacka et al, 2011 ; Bhattarai and Dai, 2017 ; Li Y. et al, 2020 ; Li et al, 2021 ). Additionally, the excellent biocompatibility and low toxicity make them a great candidate for biological studies spanning from imaging to therapy.…”
Section: Cyanine Dyes In Phototherapiesmentioning
confidence: 99%
“…Cyanine fluorophores, especially those excited with a light in the NIR, are studied for both fluorescence imaging and phototherapeutic effect, which renders them as phototheranostic agents ( Jung et al, 2018 ; Chen et al, 2019 ; Li et al, 2021 ). However, the phototherapeutic efficacy of conventional cyanine dyes is not adequate due to low photoconversion efficiency, poor photostability, and undesired aggregation in aqueous solution.…”
Section: Cyanine Dyes In Phototherapiesmentioning
confidence: 99%
“…The organic PSs harbor the special merits of good biocompatibility and biodegradability. Various organic nanomaterial-based PSs, such as porphyrin [ [71] , [72] , [73] , [74] , [75] ], boron dipyrromethene (BODIPY) [ [76] , [77] , [78] ], cyanine dyes [ [79] , [80] , [81] , [82] ], aggregation-induced emission (AIE) molecules [ [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] ], have attracted considerable attention.…”
Section: Reactive Oxygen Species-based Antitumor Therapymentioning
confidence: 99%
“…As an FDA-approved photosensitizer, indocyanine green (ICG) has attracted wide interest due to its photothermal and photodynamic therapeutic characteristics [ 20 ], because it can efficiently convert the absorbed NIR laser energy into heat [ 21 ] and produce ROS as well [ 22 ]. Duan et al employed monolayered-double-hydroxide (MLDH) to load ICG and DOX, and demonstrated their excellent tri-modal synergetic anticancer activity [ 23 ].…”
Section: Introductionmentioning
confidence: 99%